Source Rock Evaluation of Paleocene Akinbo shale, Eastern Dahomey Basin - Victoria, Dairo; Onenu, Asue (International Journal of Advanced Geosciences, 2017)
Selected subsurface core samples of the shale of Akinbo Formation as penetrated by an exploratory well in Ibese, Eastern Dahomey basin were investigated to ascertain the quality and quantity of organic matter, the hydrocarbon potential and kerogen type.The samples were subjected to Total Organic Carbon (TOC) and Rock Eval analyses and various cross plots were generated from the data obtained.The TOC and Free oil content (S1) of all the shale samples range from 0.96wt% to 2.82wt% and 0.07mgHC/g to 0.17mgHC/g with mean values of 1.67wt% and 0.11mgHC/g respectively while the source rock potential (S2) ranges from 0.01mgHC/g to 0.17mgHC/g with an average value of 0.08mgHC/g. Also, the Hydrogen Index (HI) and the Oxygen Index (OI), ranges from 0.35mgHC/g TOC to 16.7mgHC/g TOC and 11.4mgCO/g TOC to 38.33mgCO/g TOC with an average value of 5.77mgHC/g TOC and 19.04mgCO/g TOC respectively. The Production Index (PI) and the Generative Potential (GP) range from 0.38 to 0.94 and 0.12mgHC/g to 0.34mgHC/g with mean values of 0.61 and 0.19mgHC/g respectively.The results obtained from the cross plots of HI versus OI, S2 versus TOC and TOC versus GP; It shows that the shale samples from the Akinbo Formation have good organic matter richness to generate hydrocarbon, dominantly gas prone and from a Type III kerogen.